Cement mortar reinforced with reclaimed carbon fibres, CFRP waste or prepreg carbon waste. (15th November 2016) - Nguyen, Hoang; Carvelli, Valter; Fujii, Toru; Okubo, Kazuya
Highlights: Mechanical behaviour of RCF, CFRP waste or prepreg waste reinforced cement mortar. Mortar with CFRP or PW wastes exhibited a softening behaviour. The fracture toughness was extremely improved by 3% of CFRP or 2% of PW. Shrinkage macro cracks did not appear in materials with CFRP or PW after 28 days. Abstract: This experimental investigation deals with the effects of reclaimed carbon fibres (RCF), carbon fibre reinforced polymer (CFRP) waste, and prepreg carbon waste (PW) of different contents on the mechanical properties of Portland cement mortar. The mechanical properties of reinforced cement mortars were measured by bending, compression and fracture toughness tests. Moreover, the shrinkage behaviour was observed by restrained drying shrinkage test. The influences of dispersing agent and additives for cement, including mineral and chemical admixtures, were evaluated for a total of 18 different combinations.